YURIY MAMLEEV’S CREATIVE WRITINGS: PHILOSOPHY AND / OR LITERATURE? - Honcharov, Semen A. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The author of the article studies the creative legacy of Yuriy Mamleev, trying to establish the correlation between of his philosophical and fiction writings. The conventional editorial distinction between philosophical and literary texts as different and autonomous categories (where philosophical texts are “The Destiny of Being” and “Eternal Russia”, the rest are fiction) is rejected. Instead of the idea, that philosophical and fictional aspects of texts by Mamleev are inextricably linked, it is claimed that they should be considered together. In the author’s opinion, these texts present different perspectives and implementations of his oeuvre that contains the rational dimension (which requires categorical language of philosophy) and on the other hand – irrational dimension of artistic images and obscure allusions. Mamleev’s writings considered by means of 5 crucial “metathemes”: Аbyss and the “Ultimate relationships” concerned with it, the Mystery which has two levels – one cognizable and the another – uncoognizable in principal, the “root of self-being” and metaphysic (utrism) of “I”, death and immortality, Russia and the Russian soul which are existed between West and East with special historical and cosmological mission. It is concluded that these 5 metathemes pervade all Mamleev’s texts and comprise his spiritual search. The characters of Mamleev’s fiction are mostly people of post-Soviet world, who ask questions with no set answers to become acquainted with the secrets of being. At the same time they are concerned with their own existence, their self destiny. Their actions are extraordinary and illogical. Supposedly Mamleev’s artistic images not only correspond with his philosophical ideas, for instance – utrism or the “Ultimate relationships”, but also reveal them from unexpected perspective. The author determines that distinction between philosophy and literature of Mamleev is incorrect, as these areas are conflated. Any distinction of this kind will ruin the logic of Mamleev’s thinking and outlook. Thus, metaphysical realism (that Mamleev founds) can be viewed as the crossing, distinction blurring area, productive and creative transgression. Or as the situation when philosophy (and literature) is more than it is itself.